Current affairs: An Inca suspension bridge is restored in Peru - Jordi Busqué (The UNESCO Courier, 2019)
Every year in the first week of June, the inhabitants of Peru’s Quehue district gather to restore the rope suspension bridge that connects the two banks of the Apurímac river. This centuries-old secular Andean tradition has been inscribed on the Representative List of the Intangible Cultural Heritage of Humanity since 2013.